2013
DOI: 10.1002/cpp.1867
|View full text |Cite
|
Sign up to set email alerts
|

Reading Group Rehabilitation for Patients with Psychosis: A Randomized Controlled Study

Abstract: Objective: Group reading activities are often reported to be helpful in a variety of psychiatric conditions. However, data on the effects of structured reading rehabilitation activities, in both hospital and community settings for patients with psychosis, are still scarce. Our aim was to investigate the effects on clinical status, disability, psychosocial functioning and cognitive functioning of a structured group reading activity, in a sample of hospitalized patients with psychosis. Methods: We enrolled 41 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
(46 reference statements)
0
5
0
2
Order By: Relevance
“…In 2013, a quantitative study, and the first known independent randomised controlled trials, evaluating the 'Get Into Reading' model was conducted in Italy, with 41 hospitalised participants with psychosis. Even though the sample size was small, results showed significant improvement in the wellbeing and symptoms of the participants (Volpe et al, 2013).…”
Section: The Success Of Creative Bibliotherapy To Effect Wellbeingmentioning
confidence: 89%
“…In 2013, a quantitative study, and the first known independent randomised controlled trials, evaluating the 'Get Into Reading' model was conducted in Italy, with 41 hospitalised participants with psychosis. Even though the sample size was small, results showed significant improvement in the wellbeing and symptoms of the participants (Volpe et al, 2013).…”
Section: The Success Of Creative Bibliotherapy To Effect Wellbeingmentioning
confidence: 89%
“…Musical activities, that involve a wide bilateral network of brain areas related to attention, semantic processing, memory and learning,31 are proved to enhance cognitive functions both in healthy subjects32 and in dyslexia,33 dementia34 and recovery from stroke 31. Group reading activities have been reported to improve cognitive and psychosocial functioning in hospitalized patients with psychosis35 and group conversation, art/drama sessions and recreational activities have been shown to ameliorate the neuropsychological performance in schizophrenic patients 36…”
Section: Discussionmentioning
confidence: 99%
“…The students also described that some of the theoretical and philosophical topics were important for them, and that reading about people in different life situations, for example, reading philosophy and history, gave them a broader view about their own lives and their problems. Dowrick et al [ 26 ] found that attending reading groups and the content of the literature has significant effects on the outcomes of patients with depression [ 26 ], and reading groups have improved cognitive and psychosocial functioning of patients with psychosis [ 27 ]. This may indicate that not only participating in an activity but also the content of the activity might have affected the students.…”
Section: Discussionmentioning
confidence: 99%